IDENTIFIKASI KESULITAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA DI MI AL AHYAR BAGIK POLAK NTB (Jurnal Pendidikan Dasar, 2019)
This study aims determine “ learning difficulties in Mathematics Subjects In Polak Bagik 2019 Academic Year. In this study researchers used a qualitative approach because the data obtained in the field are data that produce descriptive data in the form of information or information relatedtoexisting titles not in the form of numbers. The data collection methodes used are the method of observation, interviews, and documentation. Inductive data analysis techiques, by means of collecting data, reducting data, presentinfg data and drawing conclusions, and validating the data is done by triangulation and sufficiency of references. The result this study indicate the student have difficulty learning n the operation of mathematical numbers, calculation, understanding problem language and difficuly working on mathematical formulas. Faktor that cause student learning difficulties, come from internal factor and external factors. The teacher strive to overcome student learning difficulties by doing remedial or inprovement, providing and learning motivation.